Unentangling gender stereotypes in visual culture: the short film Purl (2019) and dissent from Toxic Masculinity (Revista Apotheke, 2023)
From their first days of life, even as babies, the subjects live in physical and symbolic spaces traversed by images of different types of media, which, in addition to decorating and theming environments, end up perpetuating paradigms. Such artifacts tend to be equally efficient at presenting and characterizing children based on the gender they are assigned: either a girl or a boy. In this text, in particular, we are concerned with an artifact that, instead of reinforcing gender stereotypes, naturalizing them, puts them in check. We refer, in this case, to the animation Purl (2019): a short film produced by the company Pixar and directed and written by Kristen Lester, and which thematizes the notion of toxic masculinity. In what ways that toxic masculinity and other issues related to gender relations are presented in the short film Purl (2019)? To respond to this research problem, this article aims to reflect on artifacts of children’s visual culture that lend dissidence to gender stereotypes. The theoretical foundation supports two Cultural Studies and Visual Culture Studies, in interfaces with the Masculinities Studies, giving emphasis to Education and more specifically to the Teaching of Visual Arts. Structurally, the discussion was organized in two moments. First, we highlight concepts from two Studies on Masculinities and explain, methodologically, the extraction of screenshots from Purl (2019), and after that, we share the analysis, confronting and/or approximating images of the short footage with reflections from the previously mentioned field of research. In the analysis, we contemplate 27 screenshots taken from the short footage. Sublinha-se, finally, the need for dissident experiences of Ensino de Arte that sublinhem the pedagogical and political character of visual culture straightened out children.
Keywords: cultural studies; masculinity; education; visual culture; childhoods